IMPACT OF SOCIAL MEDIA USE, AGE AND GENDER ON ACADEMIC PERFORMANCE OF TEENAGE UNDERGRADUATES IN IMO STATE - Dike, Oluchi Gabriela; Ibeh, Paschal Onyinyechi; Ernest- Samuel, Gloria Chimeziem (African Journal of Social and Behavioural Sciences, 2024)
This study examined the impact of social media usage, age and gender on the academic performance of teenage undergraduates at three selected universities in Imo State. Using a cross-sectional survey design, the instruments used were the Gupta and Bashir (2018) Social Networking Usage Questionnaire (SNUQ), 100-point results were used to evaluate academic performance, and a self-constructed questionnaire assessed the sociodemographic characteristics of the 406 respondents. The respondents comprised 206 males and 199 females aged 17 to 19 years, with a mean age of 18.87 years and a standard deviation (SD) of 5.02. The collated data were statistically analysed using Pearson correlation, multiple regression analysis, and one-way ANOVA. The findings of the study revealed that social media is significantly a negative predictor of academic performance of teenage undergraduates. Age and gender were not implicated on the academic performance of the teenage undergraduates. The study recommended that the dangers of social media use be incorporated into the orientation programs and course introductions of undergraduates in schools, as universities address general issues related to students’ poor academic performance.